Antimelanoma effect of a fucoxylomannan isolated from Ganoderma lucidum fruiting bodies. (15th October 2022) - da Silva Milhorini, Shayane; de Lima Bellan, Daniel; Zavadinack, Matheus; Simas, Fernanda Fogagnoli; Smiderle, Fhernanda Ribeiro; de Santana-Filho, Arquimedes Paixão; Sassaki, Guilherme Lanzi; Iacomini, Marcello
Abstract: A fucoxylomannan (FXM) was isolated from the mushroom Ganoderma lucidum through alkaline extraction followed by dialysis, freeze-thawing, and fractionation by Fehling's solution. The main chain of FXM presented α-d -Man p- (1→4)-linked units, and some of them were branched at O-6 position by α-l -Fuc p -(1→2)-β-d -Xyl p groups. Its M w was 35.9 kDa. FXM was tested on melanoma B16-F10 cells and it showed cell viability and cell density reduction, as well as antiproliferative effect, through cell cycle arrest. Additionally, the anchorage-independent clonogenic capacity of such cells was significantly reduced by FXM, decreasing the number of cells by colony and the colonies area. No effect on viability neither in proliferation of non-tumoral Balb c/3T3 fibroblasts was observed. These results indicate that FXM is a promising anti-proliferative compound impairing pivotal tumorigenic mechanisms, eliciting this polysaccharide to be further explored as an antimelanoma drug. Highlights: A fucoxylomannan was obtained from Ganoderma lucidum mushroom. It has a main chain of α-d -Man p- (1→4), branched at O-6 by α-l -Fuc p -(1→2)-β-d -Xyl p. It showed antiproliferative effect on B16-F10 cells, but not in Balb c/3T3 cells. It showed cell cycle arrest, as well as reduction of colonies area of B16-F10 cells.